Sistem Pengambilan Keputusan Kelayakan Penerima Bantuan Sosial di Desa Menggunakan Metode Kombinasi AHP-SAW - Sandi Tian Ari Kusuma; I Gusti Nyoman Yudi Hartawan; Sariyasa Sariyasa (Universitas Muhammadiyah Surabaya, 2025)
This study aims to implement and measure the accuracy of the combined Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods in making decisions about providing social assistance in Purwoagung Village. This study is a type of applied research that focuses on solving real problems practically by utilizing data obtained from the village government. Data were collected through observation, interviews, questionnaires, and documentation studies to ensure the validity and completeness of the information. In its implementation, data were analyzed through the stages of data mining, criteria weighting using AHP, and alternative ranking using the SAW method. The results showed that of the six criteria used, the head of the family's occupation had the highest weight (0.453), followed by home ownership status, number of dependent children, savings ownership, cooking fuel, and type of house floor. The alternative with the highest preference value of 0.866 was determined as the main priority recipient, while the lowest alternative obtained a value of 0.325. Accuracy testing using a confusion matrix showed an accuracy level of the AHP-SAW method of 92.11%, indicating very good classification performance. These results prove that the AHP-SAW method is effective in determining the eligibility of social assistance recipients objectively, systematically, and efficiently. This study recommends further development with additional methods to improve the accuracy and use of the results of this study by the village in preparing policies for the distribution of social assistance that are more targeted, fair, and transparent. Keywords: social assistance, community, Purwoagung Village, AHP – SAW method.